2014
DOI: 10.1002/pro.2542
|View full text |Cite
|
Sign up to set email alerts
|

Iron inhibits Escherichia coli topoisomerase I activity by targeting the first two zinc‐binding sites in the C‐terminal domain

Abstract: Escherichia coli DNA topoisomerase I (TopA) contains a 67 kDa N-terminal catalytic domain and a 30 kDa C-terminal zinc-binding region (ZD domain) which has three adjacent tetracysteine zinc-binding motifs. Previous studies have shown that E. coli TopA can bind both iron and zinc, and that iron binding in TopA results in failure to unwind the negatively supercoiled DNA. Here, we report that each E. coli TopA monomer binds one atom of iron via the first two zincbinding motifs in ZD domain and both the first and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Our previous studies have shown that topoisomerase I (17, 18) and its homolog YrdD (19) are iron and zinc binding proteins, and excess zinc can easily compete for iron binding in the proteins in vivo (17, 19). This suggests that zinc and iron may have similar binding sites in proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have shown that topoisomerase I (17, 18) and its homolog YrdD (19) are iron and zinc binding proteins, and excess zinc can easily compete for iron binding in the proteins in vivo (17, 19). This suggests that zinc and iron may have similar binding sites in proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the peptide motif Glu-Xaa-Xaa-Glu was found to play a role in the direct binding of ferric iron in several proteins involved in iron transport, sensing, and storage [ 45 ]. The glutamate and histidine residues together form a functional domain for the iron-binding site [ 46 ]. The loop ring between the seventh and eighth transmembrane domains is the second highly variable region (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To purify the protein, the culture was pelleted, and bacterial cells were resuspended in Tris buffer (20 mM Tris-HCl, 500 mM NaCl, pH 8.0) before being disrupted by a high-pressure homogenizer (JNBIO). The lysate was then centrifuged at 15,000 × g for 45 min, and the His 6tagged (6 × histidine tag) soluble proteins in the supernatant were purified using a Ni-agarose column (Qiagen co.), followed by a gel filtration column (SuperdexTM 75 10/300GL, GE), as described in Wang et al (2014). The purity of the purified protein was analyzed using SDS/PAGE gel stained by Coomassie brilliant blue.…”
Section: Protein Purificationmentioning
confidence: 99%